The protection of “state overseas interests” in China’s foreign policy strategy: conceptual, legal and expert dimensions of the discussion - Sizov G.A. (Восточная Азия: факты и аналитика)
The article examines the content of “state overseas interests”, which is an important Chinese diplomatic concept, and studies the role those interests play in the country's foreign policy strategy. The work analyzes a relatively wide range of Chinese research literature, conceptual and regulatory documents related to the PRC’s policy to protect its overseas interests. The author concludes that the Chinese leadership adheres to a narrow materialistic interpretation of overseas interests and does not regard their protection as an existential need as compared to the “core interests” of the country. At present, Beijing's pursuit of its overseas interests exhibits protective nature and is aimed at promoting country’s economic development, implementing foreign economic initiatives, improving international image and deepening its relations with other states. This situation is unlikely to change in the foreseeable future, but the emergence of more serious threats to China's overseas interests may bring about new changes in the country's foreign policy strategy.